2015
DOI: 10.1073/pnas.1506101112
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic physical interactions map kinetochore regulators and regions sensitive to constitutive Cdc14 localization

Abstract: The location of proteins within eukaryotic cells is often critical for their function and relocation of proteins forms the mainstay of regulatory pathways. To assess the importance of protein location to cellular homeostasis, we have developed a methodology to systematically create binary physical interactions between a query protein and most other members of the proteome. This method allows us to rapidly assess which of the thousands of possible protein interactions modify a phenotype. As proof of principle w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 58 publications
5
52
1
Order By: Relevance
“…We confirmed that Pkc1-GBP was co-localizing with endogenously GFP-tagged kinetochore using fluorescence imaging. We found that the GFP-GBP binding is sufficient to cause considerable relocalization of Pkc1 to the kinetochore in all cases (Fig 5A), consistent with previous observations (Berry et al, 2016; Olafsson & Thorpe, 2015). We found that a number of haploid strains, which contain only a single endogenously encoded copy of the GFP tagged protein, are restricted, for growth when expressing Pck1-GBP.…”
Section: Synthetic Physical Interactionssupporting
confidence: 92%
See 4 more Smart Citations
“…We confirmed that Pkc1-GBP was co-localizing with endogenously GFP-tagged kinetochore using fluorescence imaging. We found that the GFP-GBP binding is sufficient to cause considerable relocalization of Pkc1 to the kinetochore in all cases (Fig 5A), consistent with previous observations (Berry et al, 2016; Olafsson & Thorpe, 2015). We found that a number of haploid strains, which contain only a single endogenously encoded copy of the GFP tagged protein, are restricted, for growth when expressing Pck1-GBP.…”
Section: Synthetic Physical Interactionssupporting
confidence: 92%
“…The fluoresecence intensity within a ~600 nm square box in the focal plane of each foci is measured and a local background signal for each focus is subtracted. We found that the deviations in fluorescence intensity of control strains across each 48 pad imaging plate and consequently we used a smoothing algorithm to normalize values across each plate of the screen (Olafsson & Thorpe, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations